A literature review and meta‐analysis of drug company–funded mental health websites. (10th May 2013) - Read, J.; Cain, A.
Abstract : Objective: The pharmaceutical industry exercises pervasive influence in the mental health field. The internet has become a primary source of mental health information for the public and practitioners. This study therefore compared mental health websites funded and not funded by drug companies. Method: A systematic literature review of studies examining the role of drug companies in the funding of mental health websites was conducted, followed by a meta‐analysis of studies comparing drug company–funded (DCF) sites with sites not funded by the industry. Results: Mental health websites, in general, overemphasize biogenetic causal explanations and medication. Many mental health websites (42%) are either drug company owned (6%) or receive funding from drug companies (36%). A meta‐analysis found that DCF sites are significantly more biased toward biogenetic causes ( P < 0.01) and toward medication ( P < 0.0001) than sites that are financially independent of the industry. Conclusion: Practitioners are encouraged to inform patients about the bias inherent in industry‐sponsored websites and to recommend, instead, more balanced websites that present a range of evidence‐based information about causes and treatments.